Early access provision: Awareness, educational needs and opportunities to improve oncology patients’ access to care - Krendyukov, Andriy; Singhvi, Sanjay; Green-Morrison, Yianick; Zabransky, Markus (Frontiers in Oncology, 2022)
Background An unmet medical need exists for many oncology patients who cannot be treated satisfactorily by available therapeutic options. Early access provision (EAP) is endorsed by competent authorities to improve patient access to innovative medicinal products (InMPs). This paper determined awareness and understanding among practicing physicians of integrated EAP protocols, and of the procedures involved in EAP applications for oncology trials prior to marketing authorization. Methods An on-line, fully anonymous survey reaching out to more than 3,258 physicians (including practicing oncologists) was initiated between November 2020 - January 2021. Participants were questioned about their knowledge and understanding of EAP and the decision processes involved, level of experience, interest for further educational activities and opportunities to improve the process, both in general and specifically during the COVID-19 pandemic. The frequency of EAP protocols for oncology InMPs was identified by a search of ClinicalTrials.gov and EU Clinical Trials registers. Results Survey results (75% oncologists) indicated 75% of respondents were ‘very comfortable’ or ‘comfortable’ with using EAP for their patients, but only 54.5% correctly answered the specific knowledge-based question related to the EAP definition. For 56% of respondents, experience with EAP in daily practice was very limited. Two-thirds indicated an average or lower level of understanding about the application process and regulatory requirements involved (65.2% and 66.0%, respectively). Knowledge on data collection and serious adverse event reporting under EAP was lower at 57.8% and 50.5% of respondents, respectively. Awareness of physician responsibilities was high in 59.7% of respondents, but fewer understood roles and responsibilities of manufacturing companies (31.2%). Most indicated they would consider clinical efficacy and safety data from comparative phase III randomized controlled trials as of high importance to support their decision to apply for EAP (93.4% and 86.8%, respectively). During the COVID-19 pandemic, the majority of respondents highlighted the need to improve and adapt EAP with regard to the application process and documentation (83.8%), InMP supply and logistics (88.4), and safety reporting process (78.0%). Of identified oncology trials with a ClinicalTrials.gov protocol, only 149 (0.4%) included EAP, and 23 used the data to receive a marketing authorization during the period Jan 2015 to December 2020. Of oncology trials with a EudraCT protocol, only 21 (0.23%) included EAP, of which 6 were used to receive a conditional or full marketing authorisation over the same period. Conclusion Use of EAP in daily practice remains limited. Challenges posed by the EAP process, together with a lack of education on this topic, might contribute to its under-utilization and influence access of oncology patients to care. Continuous educational efforts from different stakeholders are required to better inform and support practicing oncologists during the EAP application process and regulatory framework follow up. Education should also be provided on EAP roles and responsibilities, monitoring, and potential adaptations when faced with specific challenges, such as the current COVID-19 pandemic.